The battles against locusts: new insecticides sought - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Last year the Sahelian countries again fell victim to attacks by locusts. This time the desert locust populations (Schistocerca gregaria) - devastated by massive doses of insecticide and by cold and drought - posed little threat, but the various...